Correlation of climatic factors with cereal crops yield: a study from historical data of Morang district, Nepal - Khanal, Badri (Journal of Agriculture and Environment, 2015)
The present study is based on the secondary sources of information on temperature, rainfall and productivity of four major cereals (Rice, Maize, Finger Millet and Wheat) in Morang district of Nepal. A total of 17 years data (1995-2011) on yield of crops, annual total rainfall, annual mean maximum temperature and annual mean minimum temperature is analysed. The suitability analysis of crops shows that all the four cereals found to be suitable for cultivation in temperature range of Morang district, whereas irrigation is required in addition to recorded rainfall in case of rice and wheat. The production of three cereals except millet (which is almost stable) has increased during the study period. The analysis of correlation coefficient shows that maize yield and minimum temperature have strong positive correlation (0.7755). The linear regression analysis showed that the yield of maize was significant and highly sensitive to combined effect of all three climatic factors (R2 0.7414). Whereas, the yield of rice, millet and wheat were not statistically significantly related. At individual climatic factors level, yield of maize and wheat were significantly related with annual mean minimum temperature. The yield of these crops can be increased by crop management mainly by altering the planting time, varieties and irrigation practices.